A framework for a low‐cost system of automated gate control in assays of spatial cognition in fishes - Valerie Lucks; Jens Theine; Maria Paula Arteaga Avendaño; Jacob Engelmann (Journal of Fish Biology, 2025)
Automation of experimental setups is a promising direction in behavioral research because it can facilitate the acquisition of data while increasing its repeatability and reliability. For example, research in spatial cognition can benefit from automated control by systematic manipulation of sensory cues and more efficient execution of training procedures. However, commercial solutions are often costly, restricted to specific platforms, and mainly focused on the automation of data acquisition, stimulus presentation, and reward delivery. Animal welfare considerations as well as experimental demands may require automating the access of an animal or animals to the experimental arena. Here, we provide and test a low‐cost, versatile Raspberry Pi‐based solution for such use cases. We provide four application scenarios of varying complexities, based on our research of spatial orientation and navigation in weakly electric fish, with step‐by‐step protocols for the control of gates in the experimental setups. This easy‐to‐implement, platform‐independent approach can be adapted to various experimental needs, including closed‐loop as well as field experiments. As such, it can contribute to the optimization and standardization of experiments in a variety of species, thereby enhancing the comparability of data.

Comparative histology of the adult electric organ among four species of the genus Campylomormyrus (Teleostei: Mormyridae) - Christiane Paul; Victor Mamonekene; Marianne Vater; Philine G. D. Feulner; Jacob Engelmann; Ralph Tiedemann; Frank Kirschbaum (Journal of Comparative Physiology A, 2015)

Receptive field properties of neurons in the electrosensory lateral line lobe of the weakly electric fish, Gnathonemus petersii - Michael G. Metzen; Jacob Engelmann; João Bacelo; Kirsty Grant; Gerhard von der Emde (Journal of Comparative Physiology A, 2008)

Electric imaging through active electrolocation: implication for the analysis of complex scenes - Jacob Engelmann; João Bacelo; Michael Metzen; Roland Pusch; Beatrice Bouton; Adriana Migliaro; Angel Caputi; Ruben Budelli; Kirsty Grant; Gerhard von der Emde (Biological Cybernetics, 2008)

Object localization through the lateral line system of fish: theory and experiment - Julie Goulet; Jacob Engelmann; Boris P. Chagnaud; Jan-Moritz P. Franosch; Maria D. Suttner; J. Leo van Hemmen (Journal of Comparative Physiology A, 2008)